Diversity of plants, bee pollinators, and their interaction networks along an elevation gradient of the Eastern Afromontane biodiversity hotspot in Kenya - Pirk, Christian Walter Werner (University of Pretoria, 2023)
Thesis (PhD (Entomology))--University of Pretoria, 2022.